STUDY OF ELEMENTS OF HARA MACRO ON AGRICULTURE IN VILLAGE WAIHERU RT 06 RW 008 KECAMATAN BAGUALA AMBON CITY 2017 - Wa Rina (Communication and Social Dinamics (CSD), 2020)
Soil fertility is largely determined by the presence of nutrients in the soil, both macro nutrients, secondary nutrients and micro nutrients. Macro nutrients include nitrogen (N), phosphorus (P), potassium (K), and C, H, O. The research objective was to determine the nutrients of Phosphorus, Potassium, C-organic and pH on Agricultural Land in Waiheru Village RT 06 RW 008. The research design was descriptive research with the method used was colorimetry adjusted to the PUTK color chart. The population is the agricultural land area of Waiheru Village, RT 06 RW 008, with a sample of 5 points in part of the land in the area. Results Phosphorus 4 point nutrient content is high in blue, and 1 bladder point is bluish. Potassium content of 3 points has a high colored content of fog, 1 point contains a little fog and 1 tittik is marked with no fog. The content of organic C is 1 point with a medium content with high foam in the test tube reaching more than 3 cm, while the 4 point content is low characterized by foam height in the test tube less than 3 cm and the soil pH content of 4 points is somewhat acidic colored yellow, and 1 acidic pH point marked orange. Suggestions that farmers should give time to rest on the ground and use fertilizer according to their needs. Keywords: agricultural land; macro nutrients ABSTRAK Kesuburan tanah sangat ditentukan oleh keberadaan unsur hara dalam tanah, baik unsur hara makro, unsur hara sekunder maupun unsur hara mikro. Unsur hara makro meliputi nitrogen (N), fosfor (P), kalium (K), dan C,H,O. Tujuan penelitian adalah untuk mengetahui unsur hara Fosfor, Kalium, C-organik dan pH pada Lahan Pertanian Di Desa Waiheru RT 06 RW 008. Rancangan penelitian adalah penelitian penelitian deskriptif dengan metode yang digunakan adalah kolorimetri disesuaikan dengan bagan warna PUTK. Populasi yaitu area lahan pertanian Desa waiheru RT 06 RW 008 dengan sampel sebagian tanah di area lahan sebanyak 5 titik. Hasil Kandungan unsur hara fosfor 4 titik kandungannya tinggi berwarna biru, dan 1 titik kandunganya sedang berwarna kebiruan. Kandungan unsur hara kalium 3 titik kandungannya tinggi berwarna ada kabut, 1 titik kandungannya sedang berwarna sedikit kabut dan 1 tittik rendah ditandai warna tidak ada kabut. Kandungan C-organik terdapat 1 titik yang kandungannya sedang dengan tinggi busa pada tabung reaksi mencapai lebih dari 3 cm, sementara 4 titik kandungannya rendah ditandai dengan tinggi busa pada tabung reaksi kurang dari 3 cm dan kandungan unsur pH tanah terdapat 4 titik bersifat agak masam berwarna kuning, dan 1 titik pHnya bersifat masam ditandai dengan warna orange. Saran para petani sebaiknya memberikan waktu istirahat pada tanah serta menggynakan pupuk sesuai dengan kebutuhannya. Kata kunci: lahan pertanian; unsur hara makro